Pemberdayaan Gender Pada Tokoh Adat Untuk Mendukung Peran Perempuan Dalam Pembangunan Desa - Hadriana Marhaeni Munthe; Bisru Hafi (Journal of Education, Humaniora and Social Sciences (JEHSS), 2018)
In the Pakpak Batak community which adheres to a patriarchal culture system shows that gender reality has the potential to bring up various issues of gender inequality that have the potential to harm women's lives in the aspects of education, health, development and politics. The construction of a patriarchal culture that is not friendly to women is presented by traditional decisions which tend to be impartial to women through the authority of traditional leaders in traditional institutions. These traditional leaders in power in traditional institutions place men as traditional decision makers who often determine the social order of the people in this village. Considering the power of influence of traditional leaders whose majority of men determine the course of community order, including village development, a strategy is needed as a solution to anticipate gender gaps or inequalities that harm women. In this case, service is needed, namely gender empowerment to develop understanding of gender awareness and gender equality in traditional leaders. This is because up to now the conceptualization of the values of gender awareness and gender equality has not touched the territory of the traditional leaders in power in the traditional institutions in this village. It is hoped that after carrying out gender empowerment through service there will be a gender transformation, namely a change in mindset or views of traditional leaders who are gender-biased into gender awareness.